Spirituality Approach in Islamic Religious Education for Students: A Multidisciplinary Study - Ningsih, Nikem Kurnia; Zakaria, Ahmad Masruhan; Subhan, Moh.; Sidiq, Umar; Puansah, Irman (LETIGES, 2026)
Every child, including those with disabilities, possesses spiritual and intellectual potential that can be nurtured through spirituality-based Islamic Religious Education (PAI) aligned with their individual dispositions. This study examines an integrative multidisciplinary approach to PAI for students with disabilities by connecting Islamic educational theology, inclusive education principles, and adaptive spiritual pedagogy. Employing a qualitative case study design at SLB Kemala Bhayangkari Trenggalek, data were collected through observations, interviews, and documentation, and analysed using the Miles and Huberman interactive model. The findings indicate that spirituality-based PAI learning, as perceived by teachers, extends beyond formal worship instruction to include the cultivation of character values such as honesty, responsibility, and tolerance, adjusted to students’ abilities and types of disabilities. Spiritual elements were systematically integrated into lesson plans (RPP) and Individual Learning Programs (PPI), while instructional materials were linked to values such as patience and gratitude. Teaching methods and media were adapted using lectures, visual materials, videos, and experiential activities to accommodate diverse learning needs. Teachers also reported challenges related to students’ varying emotional conditions, which were addressed through flexible and creative instructional strategies. This study contributes an integrative conceptual framework that positions spirituality as a mediating pedagogical construct linking Islamic theology, inclusive education, and adaptive multisensory practices, offering both theoretical and practical implications for the development of more humanistic and inclusive PAI learning models for students with disabilities.